17 EFFECTS OF SOY ON POST-MENOPAUSAL WOMEN. (1st March 2005) - Dupree, K.; Basaria, S.; Ojuma, A.; Dobs, A. S.
Abstract : Complementary and alternative therapies are being increasingly used in the United States. Studies of post-menopausal women indicate that estrogen replacement improves post-menopausal symptoms such as hot flashes, night sweats, and serum lipids. Naturally occurring estrogens found in plants like soybeans are called phytoestrogens and contain isoflavonoids composed of chemicals called genistein and daidzein, which are similar to estrogen chemically and are capable of binding estrogen receptors and exerting an excitatory or inhibitory effect. We hypothesized that isoflavones when administered to post-menopausal women will result in improved menopausal symptoms and improved quality of life. We report here on 34 women who have completed a randomized, double-blind, placebo-controlled 3-mos. clinical trial. Research participants were randomized to the active product, commercially available as Revival with 160 mg of soy, vs. placebo. Results showed that women taking the active soy compound reported improvement in their menopausal symptoms reflected by increased serum estrogen levels and decreased LH/FSH. Analysis of the participants' lipid profile also showed reduction of LDL and total cholesterol levels. We concluded that soy may have a role in post-menopausal women for control of vasomotor instability and improved cholesterol. (Data to be presented at meeting.)